2011
DOI: 10.1007/s00726-011-0858-6
|View full text |Cite
|
Sign up to set email alerts
|

Purification and identification of antioxidant peptides from the skin protein hydrolysate of two marine fishes, horse mackerel (Magalaspis cordyla) and croaker (Otolithes ruber)

Abstract: In the current study, two peptides with antioxidant properties were purified from skin protein hydrolysates of horse mackerel (Magalaspis cordyla) and croaker (Otolithes ruber) by consecutive chromatographic fractionations including ion exchange chromatography and gel filtration chromatography. By electron spray ionization double mass spectrometry (ESI-MS/MS), the sequence of the peptide from the skin protein hydrolysate of horse mackerel was identified to be Asn-His-Arg-Tyr-Asp-Arg (856 Da) and that of croake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(67 citation statements)
references
References 46 publications
4
62
0
1
Order By: Relevance
“…There is currently great interest to search for natural antioxidants as alternatives to the synthetic ones for applications in food processing, functional food development, cosmetic formulations, and therapy. One of the factors driving such a trend is the concern about potential side effects of synthetic antioxidants and consumer preference for natural antioxidants, which are perceived as relatively safe, especially those derived from edible sources [11,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…There is currently great interest to search for natural antioxidants as alternatives to the synthetic ones for applications in food processing, functional food development, cosmetic formulations, and therapy. One of the factors driving such a trend is the concern about potential side effects of synthetic antioxidants and consumer preference for natural antioxidants, which are perceived as relatively safe, especially those derived from edible sources [11,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, many protein hydrolysates and their isolated peptides, such as soybean protein (Chen et al 1996), bullfrog skin (Qian et al 2008), fish skin gelatin (Sampath Kumar et al 2011a), egg white proteins (Dávalos et al 2004), rice endosperm protein (Zhang et al 2009), loach protein (You et al 2010) and rapeseed protein (Pan et al 2009), have been found to possess antioxidant capacity. The antioxidant activity of protein hydrolysates or peptides have been ascribed to the cooperative effect of a number of properties, including their ability to scavenge free radicals, to act as metal-ion chelator, oxygen quencher or hydrogen donor and to inhibit the lipid oxidation (Moure et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[22] Moreover, peptides with lower molecular weights present a better chance of crossing the intestinal barrier and exerting biological effects. [24] Majority of the related studies suggested that most ACE-inhibitory peptides derived from food sources are approximately 150-800 Da in terms of molecular weight. [25] These findings agree with observations from other studies, thereby supporting the fact that the functional properties of ACE-inhibitory peptides are highly influenced by molecular mass.…”
Section: Purification and Identification Of Ace Inhibitory Peptide Ammentioning
confidence: 99%